Substorm activity as a driver of energetic pulsating aurora - Troyer, Riley N.; Jaynes, Allison N.; Kaeppler, Stephen R.; Varney, Roger H.; Reimer, Ashton S.; Jones, Sarah L. (Frontiers in Astronomy and Space Sciences, 2022)
Pulsating aurora are common diffuse-like aurora. Studies have suggested that they contain higher energy particles than other types and are possibly linked to substorm activity. There has yet to be a quantitative statistical study of the variation in pulsating aurora energy content related to substorms. We analyzed the inverted energy content from 53 events using the Poker Flat Incoherent Scatter Radar. To reduce the uncertainty, we split the differential energy flux into low and high energy using the limit of 30 keV. We also analyzed the lower altitude boundary of the electron density profile, characterized by a number density of > 10^10 m^-3, and used this as a proxy for high energy. We compared both of these to magnetic local time (MLT), AE index, and temporal proximity to substorm onset. There was a slight trend in MLT, but a much stronger one in relation to both substorm onset and AE index. For higher AE and closer to onset the total energy flux and flux above 30 keV increased. In addition, this higher energy remained enhanced for an hour after substorm onset. Our results confirm the high energy nature of pulsating aurora, demonstrate the connection to substorms, and imply their importance to coupling between the magnetosphere and atmosphere.